Miraculous (mis)conception: Naming Mary’s reproductive choice - Bowden, Anna M. V. (Review and expositor, 2025)
Traditional interpretations of the Annunciation emphasize the miraculous nature of Jesus’s conception with little attention to whether Mary even wanted to bear children. This article looks for traces of Mary’s reproductive choice in Luke’s gospel by re-reading Mary’s story from the social location of a woman who does not want to give birth. Drawing on feminist hermeneutics and personal experience, I begin by naming and making interpretive space for women who chose not to birth children. Second, I situate Mary within the broader historical context of women who resisted reproduction. Third, I question modern interpretive assumptions and reread Mary’s story, finding moments of reproductive choice in Mary’s response to Gabriel, her identification as a slave, her song of resistance, and her continued strife postpartum. Finally, I briefly explore another biblical woman who wished to refrain from childbirth to illustrate that Mary is not alone. This article concludes that the miraculous conception is ultimately an egregious (mis)conception. Mary is an unwilling participant in a divine reproductive plan that does not match her own.